Genetic improvement of barley at INIFAP (1985-2020) - Gonzalez Gonzalez, Miguel; Zamora Díaz, Mauro R.; Solano Hernández, Salomón; Huerta Zurita, Ramón; Gómez Mercado, René; Rojas Martínez, Israel (Revista Mexicana de Ciencias Agrícolas, 2021)
The genetic improvement of barley in Mexico began in 1954 in cooperation with the National Malt Industry, the Ministry of Agriculture and Livestock and the Rockefeller Foundation. In 1959, the first improved variety obtained by INIA’s barley program, Toluca I, was increased. Since its inception, INIFAP’s barley program has set out the objective of obtaining varieties that, given their quality and yield, satisfy the needs of both the farmer and the malting and brewing industrialists. For this reason, improvement research has focused on increasing yield, precocity and quality, as well as resistance to the most common diseases of the crop. Between 1959 and to date, the National Barley Program has released 22 varieties of barley (17 malting and 5 forage). With the creation of INIFAP in 1985, the program continued with research and the obtaining of genotypes suitable for malting and brewing. In these 35 years, great achievements in the release of varieties have been obtained, being Esperanza and Emerald the most important that, given their resistance to yellow stripe rust, allowed the production of barley for brewing under both irrigated and rainfed conditions; achieving national self-sufficiency in 2000. With these varieties, more than six million hectares were sown in Mexico, more than 300 000 ha per year and more than 50 000 families in the country were benefited.